Fibroblast growth factor and canonical WNT/β-catenin signaling cooperate in suppression of chondrocyte differentiation in experimental models of FGFR signaling in cartilage - Buchtova, Marcela; Oralova, Veronika; Aklian, Anie; Masek, Jan; Vesela, Iva; Ouyang, Zhufeng; Obadalova, Tereza; Konecna, Zaneta; Spoustova, Tereza; Pospisilova, Tereza; Matula, Petr; Varecha, Miroslav; et al. (Biochimica et biophysica acta, 2015)
Aberrant fibroblast growth factor (FGF) signaling disturbs chondrocyte differentiation in skeletal dysplasia, but the mechanisms underlying this process remain unclear. Recently, FGF was found to activate canonical WNT/β-catenin pathway in chondrocytes via Erk MAP kinase-mediated phosphorylation of WNT co-receptor Lrp6. Here, we explore the cellular consequences of such a signaling interaction. WNT enhanced the FGF-mediated suppression of chondrocyte differentiation in mouse limb bud micromass and limb organ cultures, leading to inhibition of cartilage nodule formation in micromass cultures, and suppression of growth in cultured limbs. Simultaneous activation of the FGF and WNT/β-catenin pathways resulted in loss of chondrocyte extracellular matrix, expression of genes typical for mineralized tissues and alteration of cellular shape. WNT enhanced the FGF-mediated downregulation of chondrocyte proteoglycan and collagen extracellular matrix via inhibition of matrix synthesis and induction of proteinases involved in matrix degradation. Expression of genes regulating RhoA GTPase pathway was induced by FGF in cooperation with WNT, and inhibition of the RhoA signaling rescued the FGF/WNT-mediated changes in chondrocyte cellular shape. Our results suggest that aberrant FGF signaling cooperates with WNT/β-catenin in suppression of chondrocyte differentiation.
Keywords: buněčná diferenciace; WNT; FGFR3; Receptors, Fibroblast Growth Factor; Low Density Lipoprotein Receptor-Related Protein-6; Fibroblast growth factor receptor; konfokální mikroskopie; fibroblastové růstové faktory; Chondrocytes; Animals; LDL receptor related protein 6; chondrocyty; kultivované buňky; Humans; Models, Biological; Microscopy, Confocal; beta Catenin; Differentiation; Fibroblast Growth Factor 2; protein Wnt3A; Drug Synergism; Wnt3A Protein; krysa rodu Rattus; receptory fibroblastových růstových faktorů; Cartilage; biologické modely; Rats; Chondrocyte; beta-katenin; Cells, Cultured; Cell Line, Tumor; Cell Differentiation; Limb Buds; nádorové buněčné linie; zvířata; western blotting; Wnt Proteins; končetinové pupeny; Transcriptome; transkriptom; HEK293 Cells; synergismus léků; Blotting, Western; polymerázová řetězová reakce s reverzní transkripcí; lidé; HEK293 buňky; Fibroblast Growth Factors; Signal Transduction; chrupavka; Reverse Transcriptase Polymerase Chain Reaction; signální transdukce; proteiny Wnt; fibroblastový růstový faktor 2